Research and Teaching Development of the Institute of Logistics and Informatics, 2015–2024 - Wodnicka, Monika; Kozar, Łukasz; Comporek, Michał; Misztal, Anna; Jadczak, Radosław; Jabłońska, Marta; Motowidlak, Urszula; Oleksiak, Piotr; Warwas, Izabela; Urbaniak, Bogusława (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and current development of the Institute of Logistics and Informatics at the Faculty of Economics and Sociology, University of Łódź. The authors discuss its academic and teaching traditions, focusing particularly on the last ten years.